Fault-Tolerant Control Based on Modified eXogenous Kalman Filter for PMSM - Ma, Liling; Wang, Fuxiang; Shen, Wei; Wang, Junzheng (Journal of electrical engineering & technology, 2023)
Aiming at the encoder fault of the three-phase permanent magnet synchronous motor control system, a modified eXogenous Kalman Filter (MXKF) is proposed. When there are errors in the initial state of the estimator, MXKF performs well while extended Kalman Filter leads to an unstable state of the system. For the system under the Three-phase Four-switch drive, MXKF is shown to have better fault-tolerant stability. In addition, to avoid the unexpected equilibrium points determined by the q-axis voltage equation, proper compensation is made in the filter. Finally, simulations have been done to verify the effectiveness of the proposed method in the following two cases: start-up with initial error and topology change of the drive. The results show the satisfying superiority of MXKF.